Impacts of Rice Importation on Nigeria's Economy - Abbas, Asiru Monday; Agada, Iye Gloria; Kolade, Olaoluwa (Journal of Scientific Agriculture, 2018)
This study critically examined the negative effects of importation of rice on the Nigerian economy. The study also took a look at various import policies embarked upon by the Nigerian government as inconsistency in policy is a major hurdle to long term investment in the rice sub-sector. Nigeria spends billions of Naira on annual basis to import rice with its attendant depletion of the nation’s foreign reserves and this study analyzed that this negative trend can be reversed as there are a lot of opportunities in the rice sector that will not only help the country to achieve self-sufficiency in rice production, but also transform the country from a net importer to an exporter of rice. In order to meet local demand, right investment has to be made in production, milling and grading (especially in the production of excellent quality rice that can replace imported rice), marketing, road infrastructure etc. It is recommended that farm inputs (fertilizers, improved quality seeds, pesticides etc.) should be heavily subsidized by the government at different levels as timely access to inputs can significantly raise the level of production and also lead to an increase in the quantity and quality of yield. Also, there has to be a consistent and business friendly government policy in the rice sub-sector in order to encourage investors.